Basic concepts of cellulose polymers- A comprehensive review - K Harika; K Sunitha; Pavan P Kumar; K Maheshwar; Madhusudan Y Rao (Archives of Global Professionals, 2012)
Man's pursuance for new and improved materials has been expanding with time and it can be said that it is unending. Though introduced very late in the chain of materials, polymers occupy a major place and pivotal position in our materials map today. Unfolding of the science of polymers and polymer - based materials had evoked lot of interest and made them as a class of materials for their potential use in the field of pharmaceuticals and industry based products. In recent years, an awareness and understanding of these polymers has increased based upon the following factors. As pharmaceutically active ingredients continue to become more ''potent'' the effective controlled delivery of doses have become intriguing. As a result, polymers now often constitute the major portion of many pharmaceutical dosage forms and as such can have profound impact on the reproducibility of drug release and overall performance of the dosage forms.The technical complexities associated with drug development have increased in controlled delivery due to challenges such as complex drug actives, and in cases of biotech products, stabilization of the active ingredient. The multidisciplinary understanding of polymers is thus required including technical, safety, quality, and regulatory aspects, which, prior to this effort, has not been available in a single resource. It also proposes new and innovative ways for regulatory review of polymers, which, if adopted,